(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Although there are many medications available to treat eczema, a rapid and efficient solution is still required. Ayurveda considers Vicharchika (eczema) disease condition, under Kshudrakustha (group of minor skin diseases). Aim: To assess, in an open-label clinical trial, the effectiveness of Rudra Taila in the management of Vicharchika (eczema). Materials and Methods: Clinically diagnosed patients of Vicharchika who fulfill inclusion criteria were selected from OPD of associated hospital of M.M.M. Govt. Ayu. College, Udaipur (Rajasthan). Rudra Taila was applied externally to a total of 30 individuals who were diagnosed as having Vicharchika twice daily for 60 days. Patients were selected irrespective of their age, sex, religion, occupation etc. and simple random sampling technique was followed. Response to the treatment in the recruited patients was recorded on a weekly basis and therapeutic effect was evaluated through symptomatic relief. Results: Rudra Taila, is an oil preparation, which is effective against all the major clinical symptoms of Vicharchika like Kandu (itching), Pidika (papular eruptions), Vaivarnyata (discoloration), Daha (burning sensation), Srava (oozing) Vedana (pain), and Rukshata (dryness). The study yields statistically highly significant results in symptoms like Kandu (itching) (p < 0.001), Vaivarnyata (discoloration) (p<0.001), and Rukshata (dryness) (p<0.001). Conclusion: Rudra Taila has proven to be effective in reducing the symptoms of Vicharchika, when applied for a period of 60 days.